2019
DOI: 10.1080/21691401.2019.1637886
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a inhibits proliferation, migration and invasion of paediatric neuroblastoma cells via targeting HNF4α

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles miR-34a inhibits proliferation, migration and invasion of paediatric neuroblastoma cells via targeting HNF4a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…As an miRNA member, prior studies have indicated that miR-34a is deregulated in various cancers (Li et al, 2019;Liu et al, 2020;Xiu et al, 2020). Besides, it is the first miRNA found to be directly regulated by p53 (Rokavec et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As an miRNA member, prior studies have indicated that miR-34a is deregulated in various cancers (Li et al, 2019;Liu et al, 2020;Xiu et al, 2020). Besides, it is the first miRNA found to be directly regulated by p53 (Rokavec et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…HNF4α was also found to be upregulated in all invasive mucinous adenocarcinoma (IMC) of the lung determined according to tissue array, indicating that HNF4α could be considered as a useful marker for IMC of the lung (92). HNF4α expression was also found to be increased in paediatric NB tissues and negatively regulated by miR-34a to promote cancer cell proliferation and invasion (93). A study in pancreatic cancer (PDAC) indicated that HNF4α is increased in cancer tissues compared with adjacent tissues (94).…”
Section: Regulatory Roles Of Hnf4α In Human Cancersmentioning
confidence: 96%
“…A recent analysis of clinical neuroblastoma tissue samples revealed that HNF4α promoted the invasion, metastasis, and angiogenesis of neuroblastoma cells by targeting matrix metalloproteinase 14 56 . Moreover, Li and Chen 57 reported that the overexpression of miR-34a inhibits the proliferation, migration, and invasion of human neuroblastoma SH-SY5Y cells by targeting HNF4α. Additionally, Defeng Deng et al 58 reported that the long noncoding RNA small nucleolar RNA host gene 16 plays an oncogenic role though the miR-542-3p/HNF4α axis via the RAS/RAF/ MEK/ERK signaling pathway to induce neuroblastoma growth.…”
Section: Neuroblastomamentioning
confidence: 99%